STRATEGI SUMBER PENDAPATAN YOUTUBE PREMIUM MELALUI YOUTUBE MUSIK - Azzah Haura Zayanti; Ni’mah Fajriatul Nabila; Muhammad Rizaluddin; Zhen Andika Setiawan; Pia Khoirotun Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
As one of the leading video sharing platforms, YouTube remains competitive and relevant by launching additional services such as YouTube Premium. The purpose of this research is to determine the income source strategies and forms of strategies carried out by YouTube premium through YouTube music. This type of research is qualitative. This research uses a literature study method by reviewing and analyzing several journals and books related to the strategic field of YouTube premium income sources through YouTube music. The result of this research is that YouTube Premium's revenue strategy through YouTube Music is based on a monthly subscription business model, where users pay a monthly fee to access content without advertising and additional features such as listening to music in the background or downloading content for offline playback. The form of strategy used by YouTube music to attract its customers to subscribe using YouTube premium is by providing a trial within a month. Initially users feel they don't need it and are willing to make purchases related to additional services for products they usually use for free.